Rumi : um itinerário de desenvolvimento espiritual rumo ao amor divino - Cardoso, Wanessa (2012)
This research aims at the knowledge of the spiritual development in the work of the Sufi mystic Djalal-od-Din Rumi, known as Mawlana, meaning Our Master . Born in 1207 in the Balkh province, the cradle of Persian civilization, Rumi produced several works of a mystical character, the most famous being the Masnavi, a collection of poems bearing the mystical as well as theological and philosophical treatises. A monumental work, divided into six books, containing fifty-one thousand verses. Known as the Persian Quran it was one of the works that we used in this research, as well as the book Fihi ma Fihi, which is about the inner life and spiritual teachings, which is the focus of this research. The main objective of the research is to understand the meaning of thinking with the heart, since it is the only place of spiritual knowledge, as posted by Rumi. We researched this recurring theme throughout his mystical work in the bibliographical literature. We understand what this Mystic of Love taught as being spiritual development, when he says that is can only happen by opening the spiritual heart, a place of communication with God. We also covered aspects of the philosophy of religions and the categories of Sufism, from a historical point of view as a setting for the readers, as we are at the base of Islam and the Middle Ages, and from there to the Rumi gnosis itself. We concluded that Rumi, throughout his life and work, emphasizes the character of a living religion , i.e., a religion that points to a path of development of the human potential, caused by a deep transformation, insisting that we don t learn through reason, but through a mystical body, which is the heart. Moreover, we can say that, according to Rumi, we need a path and a teacher to support all the changes, since it is a path that involves a sort of death, not a physical one, but from the little self, something very difficult and painful for the human being. You could still say that Rumi extends the spiritual development so that it is primarily experiential, insisting that humanity was born only to remember its source and its birthplace, which is God